Peran Literasi Keuangan Digital terhadap Ketangguhan Manajemen Keuangan Keluarga - Bidhari, Sandhika Cipta; Alyssa, Heidy Puspa; Azzahra, Kayila; Sawitri, Imelda Nadya (Warmadewa Economic Development Journal (WEDJ))
The digital transformation has fundamentally changed household financial management through the penetration of financial technology such as e-wallets, e-banking services, and digital-based financial applications. This study aims to analyze the influence of digital financial literacy on family financial management effectiveness by developing an applied quantitative model framework that combines digital literacy dimensions and financial management indicators comprehensively. The research used an associative quantitative approach with survey method on 30 employees of the Social Service for Women's Empowerment and Child Protection of Mojokerto Regency who actively use digital financial services. Data analysis was conducted using Partial Least Squares - Structural Equation Modeling (PLS-SEM) approach with SmartPLS version 3.0 software. The results showed that digital financial literacy has a significant but complex influence on family financial management effectiveness. Financial technology knowledge (? = 0.210) and digital financial risk understanding (? = 0.090) contribute positively, while digital money knowledge (? = -0.032) shows negative influence indicating potential consumptive risk from easy access to digital transactions. The structural model produces an R-square value of 0.075, indicating that 7.5% of variation in family financial management can be explained by the three digital financial literacy constructs. This research contributes theoretically by developing a more nuanced understanding of the relationship between digital financial literacy and household financial behavior, showing that not all aspects of digital literacy contribute positively to financial management.